Grammatical cohesion in the English to Arabic translation of political texts / Reem A. M. Lulu - Lulu, Reem A.M. (2013)
Cohesive markers help to relate words and sentences together in the text. Also, it makes the whole text united and meaningful resulting from their functions in linking the sentences. While translating from the SL to the TL, the translator may not translate the whole cohesive markers or translate them incorrectly which affect the communicative meaning of the SL. Thus, many studies have analyzed different texts at different languages by using one of the translation theories to find the better strategy of translating such cohesive markers. In this study, the researcher will make use of Halliday and Hasan (1976) model of cohesion to find the frequency of cohesive markers used in both texts, Arabic and English texts, the source texts are taken from The New York Times and The Washington Post online articles, their translated Arabic versions are taken from the online Arabic newspaper, namely, Asharq Al-Awsat. Also, the study will adopt Nida‟s translation techniques (1964) to identify the translation techniques used to translate English grammatical cohesive markers into Arabic text. The results showed that, Arabic texts used more grammatical cohesive devices than English text. The incidences of references and conjunctions are greater in Arabic text than in English text. However, the incidences of ellipsis and substitution are more in English text than in Arabic. Moreover, the three techniques of Nida are appeared in analysis, besides, two new techniques are appeared in this study. By identifying the translation techniques used in translating the cohesive markers, the translators or the linguists will be aware of these techniques. Keywords: Translation, Cohesion, texture, technique, References, Substitution, Ellipsis, Conjunction